2019
DOI: 10.3389/fnins.2019.00922
|View full text |Cite
|
Sign up to set email alerts
|

Pleasantness Ratings for Harmonic Intervals With Acoustic and Electric Hearing in Unilaterally Deaf Cochlear Implant Patients

Abstract: BackgroundHarmony is an important part of tonal music that conveys context, form and emotion. Two notes sounded simultaneously form a harmonic interval. In normal-hearing (NH) listeners, some harmonic intervals (e.g., minor 2nd, tritone, major 7th) typically sound more dissonant than others (e.g., octave, major 3rd, 4th). Because of the limited spectro-temporal resolution afforded by cochlear implants (CIs), music perception is generally poor. However, CI users may still be sensitive to relative dissonance acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Observations on CI patients with contralateral normal hearing are in line with this mechanistic explanation. CI patients appear to be sensitive to dissonance by the perception of roughness, and the information related to the temporal envelope plays an important role in distinguishing harmonicity from dissonance [ 40 ]. In our study, reducing the spectral distortions without altering the rhythmic information by CrystalisXDP sound processing strategy improved total scores, leading to the hypothesis that by providing discrete cues on roughness and beating, it could enhance global music perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations on CI patients with contralateral normal hearing are in line with this mechanistic explanation. CI patients appear to be sensitive to dissonance by the perception of roughness, and the information related to the temporal envelope plays an important role in distinguishing harmonicity from dissonance [ 40 ]. In our study, reducing the spectral distortions without altering the rhythmic information by CrystalisXDP sound processing strategy improved total scores, leading to the hypothesis that by providing discrete cues on roughness and beating, it could enhance global music perception.…”
Section: Discussionmentioning
confidence: 99%
“…Patients had been implanted for a mean duration of 8 ± 1.2 years [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] before inclusion. The hearing deprivation period before implantation was 9 ± 3.1 years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CI users perform markedly more poorly than people with normal hearing in judging melodic contours [87]. They are also poor at discriminating differences in musical harmony and in judging consonance or dissonance [88] (for a review, see [16]). Despite their limited ability to discriminate some features of music, many CI users report that they enjoy listening to music, and some play musical instruments.…”
Section: Perception Of Sound Via Cochlear Implantsmentioning
confidence: 99%
“… Landsberger et al (2020) demonstrated that SSD CI users preferred listening to music with both their NH ear and their contralateral CI despite demonstrating in the same individuals that music sounds dramatically worse when presented to only the CI ear than when presented to only the NH ear. A follow-up experiment ( Spitzer et al, 2019 ) suggests that the improvement in music perception from listening with a CI and NH ear is not because of improved perception of consonance or dissonance.…”
Section: Introductionmentioning
confidence: 99%